Enhanced suppression of saprotrophs by ectomycorrhizal fungi under high level of nitrogen fertilization - Liang, Shuang; Wang, Wei; Zeng, Xiaoyue; Wu, Ran; Chen, Weile (Frontiers in Ecology and Evolution, 2022)
Ectomycorrhizal fungi (EMF) are widespread in northern conifer forests. By competing with the free-living saprotrophic fungal and bacterial communities for limited soil nitrogen, EMF are expected to suppress litter decomposition and thus drive soil carbon accumulation. The EMF may also stimulate rhizosphere microbial growth through inputs of labile plant carbon, and subsequently contribute to the soil carbon pool via microbial necromass. Here we examined the relative strength of these two potential EMF effects in a northern conifer plantation of the Saihanba Forest, the largest plantation in China. The soil fungal and bacterial biomass, as well as their respiration, were quantified within the two types of soil cores that either allow or exclude the ingrowth of EMF. We also set up a nitrogen fertilization gradient (0, 5, 10, 15 g N m-2 y-1) in this plantation to quantify the influence of external inorganic nitrogen on the EMF effects. We found evidence that EMF inhibit the overall fungal and bacteria biomass, confirming the suppression of saprotrophs by EMF. In addition, high levels of external nitrogen fertilization (15 g N m-2 y-1) might further enhance the suppression by EMF. In contrast, the presence of EMF consistently increased soil microbial respiration across all nitrogen fertilization levels, indicating that the carbon allocated to EMF could have been largely consumed by microbial respiration and contributed minimally to the accumulation of microbial biomass. Our results also indicated that the suppression of saprotrophs by EMF may play a critical role in driving continuous soil carbon accumulation in this northern pine plantation under atmospheric nitrogen deposition.